Open access in addictions, associated data and countries collaboration - Liu, Yiming; Lucas-Domínguez, Rut; Alonso-Arroyo, Adolfo; Aleixandre-Benavent, Rafael; Valderrama-Zurián, Juan-Carlos (Advanced Notes in Information Science, 2024)
Open access (OA) publications and the publication of associated data represent fundamental pillars of open science. The existence or absence of OA and the type of access available may be contingent upon the presence or absence of associated data. The two policies of scientific production may be of interest for advancing knowledge in the field of addictions due to their significant social and health impact. This study aims to ascertain how the publication patterns of articles on addictions have evolved over the past two decades, to determine the relationship between these patterns and the presence of associated data, and to investigate whether cross-country collaboration varies depending on whether the articles are published in OA journals. In order to conduct this study, a comprehensive search was conducted using the Web of Science Core Collection database, with the objective of retrieving all articles related to addiction. Additionally, the PubMed database was consulted in order to ascertain the presence of associated data. The total number of articles published during the period between 2003 and 2022 is 67,027. Of these, 51% were published in OA journals, with the “green accepted” and “green published” routes being the most frequent. However, these routes have declined over time, with a shift towards the “gold” and “gold-hybrid” routes. The “green accepted” and “free to read” models exhibit the highest percentage of articles with associated data. Nevertheless, the different types of access, OA or non-OA, are inconsequential for a higher percentage of papers with associated data. The data indicate that there is no discernible difference between the countries’ collaborative efforts based on the publication status, with the United States exhibiting the highest level of involvement in both OA and non-OA contexts.